2002
DOI: 10.1086/344056
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Immune Restoration Disease in Human Immunodeficiency Virus Type 1–Infected Patients with Progressive Multifocal Leukoencephalopathy: Impact of Antiretroviral Therapy–Associated Immune Reconstitution

Abstract: Immune reconstitution resulting from use of highly active antiretroviral therapy in patients infected with human immunodeficiency virus type 1 (HIV-1) has been associated with a significant decrease in infectious morbidity and with improved survival. Occasionally, patients with quiescent disease due to human cytomegalovirus or nontuberculous mycobacteria may experience paradoxical worsening due to "dysregulated" restitution of the immune system (that is, immune restoration disease [IRD]). Acquired immunodefici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 30 publications
3
56
0
Order By: Relevance
“…This finding is highly relevant, as the recovery of overall immunity can cause an immune reconstitution-related inflammatory syndrome, which is a potentially fatal complication of PML in HIV-AIDS patients receiving HAART. 31 The same pattern has also been observed after discontinuation of natalizumab treatment in patients with multiple sclerosis developing PML. [32][33] In our patient, the recovery of specific immunity, and, in particular, of JCVspecific cytotoxic T-cell populations, contributed to viral control without inducing an immune reconstitution-related syndrome.…”
Section: Discussionsupporting
confidence: 57%
“…This finding is highly relevant, as the recovery of overall immunity can cause an immune reconstitution-related inflammatory syndrome, which is a potentially fatal complication of PML in HIV-AIDS patients receiving HAART. 31 The same pattern has also been observed after discontinuation of natalizumab treatment in patients with multiple sclerosis developing PML. [32][33] In our patient, the recovery of specific immunity, and, in particular, of JCVspecific cytotoxic T-cell populations, contributed to viral control without inducing an immune reconstitution-related syndrome.…”
Section: Discussionsupporting
confidence: 57%
“…However, uncritical routine use or extended high-dose use of corticosteroids may inhibit immune recovery with fatal outcome (208). In addition, activation of JCPyV replication from glucocorticoid response elements in the NCCR might further accelerate JCPyV replication and cytopathic damage.…”
Section: Jcpyv Diseasementioning
confidence: 99%
“…Nine of the patients described by De Luca et al 7 were excluded from the analysis because specific information was not reported and we were unable to obtain it from the authors. In one case series the diagnosis of PML was established by PCR for JCV in brain tissue only 10 ; hence it is possible that the total number of PML cases may have been overestimated although the detection of JCV in normal brain tissue remains highly controversial. In one patient who was described twice in a case report and a subsequent case series, 11,14 information from the case report was used in the analysis.…”
Section: Characteristics Of Patientsmentioning
confidence: 99%